2022
DOI: 10.1038/s41420-022-01118-x
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine modulates long non-coding RNA in the developing mouse heart

Abstract: Long non-coding RNAs (lncRNAs) were reported to potentially play a regulatory role in the process of myocardial regeneration in the neonatal mouse. N6-methyladenosine (m6A) modification may play a key role in myocardial regeneration in mice and regulates a variety of biological processes through affecting the stability of lncRNAs. However, the map of m6A modification of lncRNAs in mouse cardiac development still remains unknown. We aimed to investigate the differences in the m6A status of lncRNAs during mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Our previous study has identified that m6A modification on long non-coding RNAs may play a regulatory role during the regeneration and development of mouse myocardium [107]. In particular, recent studies have also identified multiple circRNAs to play a regulatory in heart injuries.…”
Section: Heartmentioning
confidence: 97%
“…Our previous study has identified that m6A modification on long non-coding RNAs may play a regulatory role during the regeneration and development of mouse myocardium [107]. In particular, recent studies have also identified multiple circRNAs to play a regulatory in heart injuries.…”
Section: Heartmentioning
confidence: 97%
“…108 In recent years, as important regulators in cardiac cells, various noncoding RNAs (ncRNAs), such as microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs) have received increasing attention. 109 The m 6 A-modified lncRNAs potentially are crucial to myocardium regeneration and cardiac development, 110 and the nuclear lncRNA NEAT1 is associated with the conserved oxygensensitive feedback in cardiomyocytes by regulating the processing of miRNA while acting on another target involved in cardioprotection. 111 Considering the fact that most ncRNA transcripts are previously unannotated and their functions and interplays are unclear, 112 transcriptomic approaches have great potential in qualifying and quantifying these unknown transcripts in a single detection.…”
Section: Cardiomyocyte−biomaterials Researchmentioning
confidence: 99%